2006
DOI: 10.1088/0965-0393/14/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Alternative simulation techniques for distortion of thin plate due to fillet-welded stiffeners

Abstract: This study aims to develop and validate a wide-ranging simulation tool to predict welding distortion in stiffened plates and shells, with particular emphasis on out-of-plane deformation. The approach adopted in this study uncouples the thermal, elasto-plastic and structural effects leading to distortion. The computational models and results are supported by realistic welding tests and appropriate measurements to validate the simulated thermal fields and out-of-plane distortions. The simplest and most computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Figure 11.2 shows that at points equidistant from the heat source on the plate, temperatures are similar, but the stiffener temperatures at corresponding distances are significantly higher. 1 This is confirmed by the thermographic study of Fig. 11.3, which shows higher temperatures over larger areas in the stiffener than in the base plate (see Fig.…”
Section: Introductionsupporting
confidence: 54%
“…Figure 11.2 shows that at points equidistant from the heat source on the plate, temperatures are similar, but the stiffener temperatures at corresponding distances are significantly higher. 1 This is confirmed by the thermographic study of Fig. 11.3, which shows higher temperatures over larger areas in the stiffener than in the base plate (see Fig.…”
Section: Introductionsupporting
confidence: 54%
“…The probable reason for this difference is the use of a constant heat transfer coefficient in air (h conv ). A literature survey [10,31,32] shows that the natural convective heat transfer coefficient is a function of temperature in some cases. Improvement in simulation results may, therefore, be expected by using a temperature dependent heat transfer coefficient.…”
Section: Thermal Simulation Resultsmentioning
confidence: 99%
“…Some research [6,7] has been dedicated entirely to thermal analysis and heat source modelling while other authors [8,9] have focussed upon welding induced stresses. With special reference to fillet-welded stiffeners, Camilleri et al [10,11] have suggested that the out-of-plane displacements can be efficiently predicted by computational means. Other workers [12,13] have predicted the residual stress state in friction stir welded panels and found that the collapse behaviour is less sensitive to advanced process effects than initial buckling of the panel.…”
Section: Introductionmentioning
confidence: 99%
“…Computational modelling has become increasingly popular over the past few decades for the prediction of various aspects of the welding process. Extensive studies have been conducted in areas fundamental to the final structure, namely residual stresses in the weld region [29,30,31], weld induced distortion [25,26,30,31] and the solidified weld geometry [10,31].…”
Section: Introductionmentioning
confidence: 99%
“…Mollicone et al [26] and Camilleri et al [31] presented dilatometer data, which indicated that the parent plate and filler material posses different coefficient of thermal expansions and, from this, it can therefore be inferred that the other thermal properties will also differ. Thus the accuracy of the simulation is only as accurate as the material property data supplied.…”
Section: Introductionmentioning
confidence: 99%